Dampak Pandemi Covid 19 Terhadap Keuntungan Usaha Kacang Sangrai UD. Merpati Di Desa Tombasian Atas Kecamatan Kawangkoan Barat - Mundung, Maurent Claudya; Maweikere, Audrey Julia Maria; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2023)
This study aims to determine the impact of the covid 19 pandemic on the profits of UD. Merpati's roasted peanut business. This research was conducted for 3 months in Tombasian Atas Village, West Kawangkoan District. The data analysis used in this research is descriptive data analysis, and primary data is used, where the data collected is studied and analyzed descriptively and presented in tabular form, to determine the difference between revenue and the amount of costs incurred. Based on the results of the study, the impact of the Covid-19 pandemic on the profit of UD Merpati's roasted peanut business shows that there are no negative results, in fact, it has a very positive impact on the business place where the profit of UD Merpati's roasted peanut business has increased by 88.32 percent, where before Covid-19 the profit of the roasted peanut business was IDR 3,399,794 and during Covid-19 the profit of the roasted peanut business was IDR 29,116,294.